Effect of Zinc Supplementation on Serum Zinc Level and Micronucleus Frequency in Bangladeshi Adult Females With Poor Socioeconomic Status - Mustafa, Tarek Golam; Monirujjaman, Md; Zabeen, Shahana; Hossain, Bakhtiar (Anwer Khan Modern Medical College Journal, 2011)
Zinc deficiency may result in increased DNA oxidation resulting in DNA breaks which leads to micronuclei formation. Therefore, micronuclei frequency in peripheral blood mononuclear cells has the potential to be an indicator for zinc status. The study was designed to explore the possibility of using micronuclei frequency (MNF) in peripheral blood mononuclear cells (PBMCs), as a biomarker for zinc status. The study was double blind and placebo controlled. Fourteen females with moderately low dietary zinc intake were randomly assigned to receive either zinc (20 mg of zinc as zinc sulfate /day) or placebo for twenty-one days. MNF of peripheral blood lymphocytes were determined by using cytokinesis-block micronucleus (CBMN) assay. Plasma zinc levels were measured using atomic absorption spectrophotometry. Zinc supplementation increased serum zinc levels (P = 0.008) and decreased cells with micronucleus (P =0.054) and micronuleus frequency (P = 0.016) in PBMCs. Individuals with higher zinc status, as achieved with zinc supplementation, have low micronucleus frequency. Keywords: MNF (Micronucleus Frequency); CBMN (Cytokinesis Block Micronucleus) Assay; PBMC (Peripheral Blood Mononuclear Cells) DOI: 10.3329/akmmcj.v1i1.7452 Anwer Khan Modern Medical College Journal 2010; 1(1): 04-08